1996
DOI: 10.1007/bf02088580
|View full text |Cite
|
Sign up to set email alerts
|

An exceptional genealogy for hereditary chronic pancreatitis

Abstract: Nearly one hundred families affected with hereditary chronic pancreatitis (HCP) have been reported in the literature. However, the fact that the disease involved only a few members of each family limits the informativeness of these reports and accounts for the infrequency and disappointing results of pathogenetic and genetic research. Our study concerned an exceptional HCP genealogy which would seem to provide an ideal model for the detection of a genetic anomaly linked to the expression of the disease. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…In contrast, mutations of anionic trypsinogen (PRSS2) or mesotrypsinogen (PRSS3) have not been found in association with chronic pancreatitis to date [Chen et al, 1999a;. Classic hereditary pancreatitis follows an autosomal dominant inheritance pattern with incomplete penetrance and highly variable disease expression [Comfort and Steinberg, 1952;Le Bodic et al, 1996a;Sossenheimer et al, 1997;Keim et al, 2001;Howes et al, 2004]. The mutations are located in three clusters within the trypsinogen sequence: in the TAP, in the N-terminal part of trypsin or in the longest peptide segment not stabilized by disulfide bonds between Cys64 and Cys139 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mutations of anionic trypsinogen (PRSS2) or mesotrypsinogen (PRSS3) have not been found in association with chronic pancreatitis to date [Chen et al, 1999a;. Classic hereditary pancreatitis follows an autosomal dominant inheritance pattern with incomplete penetrance and highly variable disease expression [Comfort and Steinberg, 1952;Le Bodic et al, 1996a;Sossenheimer et al, 1997;Keim et al, 2001;Howes et al, 2004]. The mutations are located in three clusters within the trypsinogen sequence: in the TAP, in the N-terminal part of trypsin or in the longest peptide segment not stabilized by disulfide bonds between Cys64 and Cys139 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Apart from an early age of onset and a positive family history, HP is indistinguishable from the sporadic disease. 3,4 Although pancreatitis was hypothesised to result from inappropriate activation of pancreatic zymogens in 1896 5 and the genetic nature of HP was identified in 1952, 6 the molecular basis of HP remained elusive until 1996, when a mutation in the cationic trypsinogen gene was demonstrated as being associated with HP.…”
Section: Introductionmentioning
confidence: 99%
“…However, other explanations for this must be explored because we found that the mean and median age at onset of symptoms in 128 patients from 25 kindreds with the trypsinogen R117H mutation were 13.7 years and 11 years, respectively; the age at onset ranged from 0 years to 53 years (unpublished data). Other complications, such as pseudocysts, are also seen and have been reported in 11% [7] to 17% [4] of patients in large studies and in higher proportions in smaller studies [10]. Thus, the clinical symptoms of patients with HP are similar to those of patients with other types of pancreatitis with variable age of onset and severity.…”
Section: Clinical Featuresmentioning
confidence: 71%